การพัฒนาแนวทางการดำเนินงานสู่มาตรฐานโรงเรียนส่งเสริมสุขภาพระดับเพชร ของสถานศึกษาขั้นพื้นฐาน สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาอุดรธานี เขต 4 - ขันซ้าย, วารุณี (Journal of Graduate School Sakon Nakhon Rajabhat University, 2018)
This research aims to: 1) study desirable condition of implementation towards Diamond Level Health Promotion School Standard (DLHPSS), 2) develop guidelines for DLHPSS. The study consisted of 3 phases. The Phase 1 was to study desirable condition towards DLHPSS. The sample of this studying was 216 stakeholders - school directors, heads of health affairs, health core students, and chairpersons of basic education school committee. The Phase 2 was the study of the best practices from 12 informants of three schools, which were qualified for DLHPSS. The first tools for this study were four forms of 5-rated scale questionnaires. The first one for school directors was a 65-item questionnaire with discrimination value between .30-.80 and overall reliability alpha coefficient of .98. The second one for heads of health affairs was a 65-item questionnaire with discrimination value between .30-.79 and overall reliability alpha coefficient of .97. The third one for the chairpersons was a 20-item questionnaire with discrimination value between .32-.79 and overall reliability alpha coefficient of .94. The fourth one for health core students was a 41-item questionnaire with discrimination value between .37-.80 and overall reliability alpha coefficient of .95. The second tool was a structured interview. Arithmetic means, standard deviation and percentage were used to analyze the obtained data. Findings: 1. The desirable condition of implementation towards DLHPSS was at high level as a whole and every component expressed highly desirable implementation. The highest average score for desirable condition was Standard No.3.3- work under Ministry of Public Health’s policy while the lowest average score was Standard No.1- health promotion implementation. 2. The guidelines for health promotion school towards DLHPSS had three standards- Standard No.1 - health promotion school implementation with one indicator, and Standard No.2- health implementation of health core students with two indicators. Standard No.3, the success of the implementation, consisted of No. 3.1- student’s health condition with seven indicators, No.3.2- projects for problem solving in school with 1 indicator, No.3.3- work under Ministry of Public Health’s policy with 8 indicators. The results from the evaluation of suitability, harmony and feasibility for DLHPSS guidelines were at the highest level.